McGrath Series 5 videolaryngoscope vs Airtraq DL videolaryngoscope for double-lumen tube intubation: A randomized trial. Issue 51 (December 2016) - Wan, Li; Liao, Mingfeng; Li, Li; Qian, Wei; Hu, Rong; Chen, Kun; Zhang, Chuanhan; Yao, Wenlong
Abstract: Background: Many studies have shown Airtraq videolaryngoscope provided faster tracheal intubation and a higher success rate than other videolaryngoscopes. Recently, different types of videolaryngoscopes have been reported for use in double-lumen tube (DLT) intubation. However, the advantages and disadvantages between them remain undetermined for DLT intubation. In this study, we compared the Airtraq DL videolaryngoscope with the McGrath Series 5 videolaryngoscope for DLT intubation by experienced anesthesiologists. Methods: Ninety patients with expected normal airways were randomly allocated to either the Airtraq or McGrath group. The primary outcome was DLT intubation time. The secondary outcomes were glottic view, success rate, subjective ease of intubation (100-mm visual analog scale, 0 = easy; 100 = difficult), incidence of DLT malposition, and postoperative intubation-related complication. Results: The airway characteristics were comparable between the 2 groups. Cormack and Lehane grades significantly improved with the use of the McGrath and Airtraq videolaryngoscopes, compared with the Macintosh laryngoscope. The intubation success rate on the first attempt was 93% in the Airtraq group and 95% in the McGrath group ( P  > 0.05). The intubation time in the McGrath group is longer than that in the Airtraq group (39.9 [9.1]s vs 28.6 [13.6]s, P  < 0.05). But intubation difficulty score, the incidence of DLT malposition and intubation-related complication were comparable between groups ( P  > 0.05). Conclusions: When using videolaryngoscopes for DLT intubation, the Airtraq DL is superior to the McGrath Series 5 in intubation time, but it does not decrease intubation difficulty.